Genesis and development processes of fractures in granite: Petrographic indicators of hydrothermal alteration. - Takashi Yuguchi; Yuya Izumino; Eiji Sasao (PLoS ONE)
Biotites occur with varying degrees of alteration within a granite. This study analyzes the relationships among alteration indicators, areal microvoid fractions in chloritized biotite, and macroscopic fracture frequencies in the Toki granite, central Japan, to establish the genesis and development processes of fractures in granite. Appropriate characterizations for the frequency distribution of macroscopic fractures in granite can assist in understanding potential hydrogeological applications, which contributes to safety evaluations for geological disposal and storage. Borehole 06MI03, drilled to a depth of 191 m, was used to obtain samples for the analysis. In total, 24 samples that depicted variations in the macroscopic fracture frequency were selected. Petrographic alteration indicators using biotite chloritization as innovative methods are proposed to evaluate the extent of hydrothermal alteration and fracture frequency within granites. The alteration indicators are defined as the ratio between the alteration product area and the original mineral area. Furthermore, the volume of microscopic fractures and micropores in the mineral was quantitatively characterized by the areal fraction of microvoids in minerals through image analysis. Samples with high macroscopic fracture frequencies correspond to a high number of areal microvoid fractions and large alteration indicators. Microvoids, which are the source of macroscopic fractures, occurred at temperatures between 350 and 780°C and can be evaluated by intrinsic factors, such as alteration indicators. Subsequent faulting and unloading (extrinsic factors) developed microvoids into macroscopic fractures. Intrinsic factors are used to evaluate the source of macroscopic fractures, and therefore contribute to the characterization of present and future distributions of macroscopic fracture frequencies.